Jersey City, N.J., Rev. Ordinances ch. 23, §§ 1-3 (1899) - (:unkn) unknown (My University, 1871)
Concerning the Transportation, Shipment and Landing of Gunpowder: Regulated the import of gunpowder and storage thereof. Also regulated the storage of gunpowder within the city
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER